KAIDAH PENAFSIRAN AL-QUR’AN DAN URGENSINYA DI ERA DISRUPSI - Arham, Arham Junaidi Firman (At-Tibyan: Jurnal Ilmu Alqur`an dan Tafsir, 2020)
The study of interpretation in the disruption era is done to avoid the error of interpretation so that it does not correspond to the intent of the content of the Qur'an. This is because the Qur'an as the miracle of the Prophet Muhammad saw. contains extraordinary beauty and greatness as a guideline for human beings. The rule of interpretation of the Qur'an in the disruption era is a decree that helps an interpreter or exegetes to withdraw the meaning/messages of the Qur'an and explain what is a misconception of the verses content in relation to the increasingly unexpected changes. The rules of the Qur'anic exilence can be used as guidelines in this disruption era can refer to the view of Abd ar-Rahman ibn Nasir Al-Sa'adi in his books Al-Qawaid Al-Hisan Al-Qur'anic Tafsir as quoted by Abd. Rahman Dahlan that there are five rules of the Qur'an interpretation. Meanwhile, Muhammad Chirzin in his book presents twelve rules of interpretation of the Qur'an that can be used as a guideline in the disruption era. Meanwhile, the importance of the interpretation of the Qur'an in the disruption era, namely; First, it can help a person's interpreter in revealing the expressed or implied meaning in the Qur'an, so that it can do it reveal what if it is still vague and unclear. Secondly, in order not to give the etymological meaning of the pronunciation of the Qur'an with other meanings that are not appropriate, both in the meaning of the essence and the meaning of majazi.